SPEECH DISORDER FOUND IN THE MAIN CHARACTER OF RECTOVERSO MOVIE - WaSAFITRI, DILAH OVY (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: speech disorder, stuttering, rectoverso, Malaikat Juga Tahu, abangAs human being, each individual has language skill that is different from one another. There are some factors that make language skills different, such as when people cannot communicate well with each other or in other words, speech disorder. The writer is interested in analyzing stuttering phenomenon in Rectoverso movie. Stuttering is a generic term that describes speech that does not follow normal, conventional rhythm. In this research, the writer investigates the characteristics of stuttering produced by the main character, “Abang” and the factors causing “Abang” to stutter in Rectoverso movie.The writer used qualitative research in document analysis in order to answer the research problem. The data were utterances produced by “Abang” and scenes containing of stuttering phenomenon in Rectoverso movie. The writer used the theory proposed by Lavid (2003) and Campbell & Hill (1987) to analyze the characteristics of stuttering. Moreover, the writer also used the theory proposed by Indah (2011), Lavid (2003) and Owens et. al (2007) to analyze the factors causing “Abang” to stutter.This study found that there are two characteristics of stuttering experienced by “Abang”; namely audible & silent blocking and monosyllabic whole-word repetitions. This study also found three factors causing “Abang” to stutter; stress factor, factor of neurotic famial and habit factor.It was found that mood and condition are the important aspects or factorsinfluencing “Abang” to stutter. This study suggests the readers who speak withstuttered people to be patient, understand the condition to make them comfortablewhile speaking and also create a good atmosphere or mood while speaking withstuttered people. This study also suggests the next researcher to use another movieor media to reveal the characteristics of stuttering and the factors causing peopleto stutter.